Non-mammalian collagen porous composite scaffold as well as preparation method and application thereof
By using the preparation method of non-mammalian-derived collagen and calcium phosphate, the problems of the contamination risk of collagen sources and the insufficient performance of biomaterials in the prior art are solved, and efficient and safe site preservation of therapeutic materials are achieved.
Patent Information
- Application Number
- CN202510060599.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-18
AI Technical Summary
In the prior art, the collagen used in commercial collagen composite sponges mostly come from pigs or cattle, which have problems with contaminant transmission and disease risk, and their degradation properties, mechanical strength and biological activity are not sufficient to be fully suitable for site preservation treatment.
Non-mammalian origin collagen is used to bind calcium phosphate to a specific preparation method, including dissolving collagen in acetic acid solution, adding calcium phosphate powder and crosslinking agent, and freeze-drying to form a porous composite scaffold.
A porous composite scaffold of non-mammalian origin with high porosity and good mechanical properties was achieved, which improved the degradation performance and biological activity of the scaffold, extended the action time, and was suitable for site preservation treatment.
Smart Images

Figure CN119838060A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomedical engineering, and in particular relates to a non-mammalian source collagen porous composite scaffold and a preparation method and application thereof. Background Art
[0002] After tooth extraction, a socket defect will be left. Uninterventional socket healing will lead to alveolar bone absorption and gum atrophy, which is not conducive to subsequent dental implants, dentures and other treatments, and will affect the gingival contour and facial appearance, resulting in potential loss of aesthetic effects. Therefore, after tooth extraction, site preservation treatment is often required at the same time to reduce alveolar bone absorption during subsequent healing, increase alveolar bone volume, and avoid gum atrophy. In medicine, autologous transplantation is considered the gold standard for site preservation, but because it is necessary to sample at the second surgical site of the patient, it not only faces quantity limitations, but also increases the complexity of the operation and patient pain, and is often not adopted. Commercially, collagen composite sponges prepared from components such as collagen and calcium phosphate are often used as biomaterials to fill socket defects after tooth extraction. Collagen, mainly type I collagen derived from bovine tendons or pigs, not only has good biological activity to provide a growth environment for extracellular matrix ECM-like regeneration at the defect, but its sponge scaffold also has good hemostatic properties, promotes blood clot formation, and accelerates defect healing. In addition, calcium phosphate, mainly hydroxyapatite, as the main component of bone, has the ability to promote alveolar bone regeneration and improve the mechanical properties of the composite sponge scaffold, providing support for early socket defects and avoiding collapse.
[0003] However, as mentioned above, the collagen used in commercial collagen composite sponges mostly comes from pigs or cows. Because mammals have more similarities in physiological structure and metabolic mechanism, pollutants are more easily transferred and accumulated between mammals, increasing the potential and uncertain risk of disease transmission. At present, extracting collagen from non-mammalian tissues such as aquaculture organisms is considered a feasible supplement, which not only avoids the shortcomings of collagen from pigs or cows, but also effectively utilizes aquaculture resources to achieve the development of green economy and blue economy.
[0004] The present invention is a further development and improvement based on the U.S. patent "COMPOSITE SCAFFOLD MATERIAL" (publication number: US2023 / 0158212A1) and the Chinese patent "Composite material scaffold" (publication number: CN115397920A). The prior patent provides a method for obtaining collagen from non-mammalian sources and a preparation method and use of a collagen-calcium phosphate composite scaffold of non-mammalian origin, achieving rapid, efficient and high-yield extraction of undenatured collagen from non-mammalian sources, and describing the potential of collagen-calcium phosphate composite scaffolds of non-mammalian origin for bone tissue engineering. However, the composite scaffold provided by the prior patent is not fully suitable for site preservation treatment due to its limitations in degradation performance, mechanical strength and biological activity, and needs to be adjusted according to the oral environment. Summary of the invention
[0005] The primary purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing a non-mammalian source collagen porous composite scaffold.
[0006] Another object of the present invention is to provide a non-mammalian source collagen porous composite scaffold obtained by the above preparation method.
[0007] Another object of the present invention is to provide an application of the above-mentioned non-mammalian source collagen porous composite scaffold.
[0008] The purpose of the present invention is achieved by the following technical solution: A method for preparing a non-mammalian source collagen porous composite scaffold comprises the following steps:
[0009] (1) dissolving non-mammalian collagen in an acetic acid solution, then adding calcium phosphate powder and mixing, and then adding a cross-linking agent to obtain a pre-solution I;
[0010] (2) After the pre-solution I is fully mixed at 0-10° C., it is added into the mold and freeze-dried to obtain a scaffold embryo;
[0011] (3) dissolving non-mammalian collagen in an acetic acid solution, and then adding a cross-linking agent to obtain a pre-solution II;
[0012] (4) Injecting the pre-solution II into the scaffold embryo obtained in step (2), allowing to react at 0-10° C., and freeze-drying to obtain a non-mammalian collagen porous composite scaffold.
[0013] The non-mammalian collagen described in step (1) and step (3) is preferably prepared by the following steps:
[0014] 1) Cleaning the fresh raw material from non-mammals, sequentially subjecting it to alkali treatment, washing, acid treatment, and mechanical crushing to obtain a mixed paste;
[0015] 2) diluting the mixed paste obtained in step 1) with water, and then centrifuging at 2-8° C. to obtain an upper layer solution containing collagen and a pellet containing pigment, and collecting the upper layer solution containing collagen;
[0016] 3) adding an inorganic salt to the upper layer solution obtained in step 2), mixing well and then standing to obtain a precipitate containing collagen, and collecting the precipitate by centrifugation;
[0017] 4) mixing the collagen-containing precipitate obtained in step 3) with an acidic solution to obtain a mixed solution containing free collagen; dialyzing the mixed solution containing free collagen to obtain a non-mammalian source collagen solution, and freeze-drying to obtain non-mammalian source collagen.
[0018] The non-mammal mentioned in step 1) can be a frog culture species, such as bullfrog (Ranacates beiana), wood frog (Rana amurensis Boulenger), tiger frog (Hoplobatrachus rugulosus, Hoplobatrachus tigerinus).
[0019] The raw material in step 1) is preferably skin.
[0020] The specific steps of the alkaline treatment in step 1) are as follows: soaking the cleaned fresh non-mammalian raw material in an alkaline solution.
[0021] The alkaline solution in the alkali treatment in step 1) is preferably a NaOH solution; its concentration is preferably 0.1-1 mol / L, 0.3-0.7 mol / L, 0.4-0.6 mol / L, 0.5 mol / L.
[0022] The ratio of the raw material to the alkaline solution in the alkali treatment in step 1) is preferably 0.1-2 g:10 mL, 0.5-1.5 g:10 mL, 1 g:10 mL.
[0023] The temperature of the alkali treatment in step 1) is 0-10°C; preferably 1-8°C, 2-6°C, 3-5°C, 4°C.
[0024] The time of the alkali treatment in step 1) is preferably at least 24 hours; more preferably 24 to 72 hours, 36 to 60 hours, 45 to 50 hours, or 48 hours.
[0025] The degree of washing in step 1) is washing until the pH value is neutral or close to neutral.
[0026] The washing solvent is deionized water or an acidic solution.
[0027] The acidic solution is preferably HCl solution.
[0028] The specific steps of the acid treatment in step 1) are as follows: soaking the washed raw material in an acidic solution.
[0029] The acidic solution for the acid treatment in step 1) is preferably an acetic acid solution.
[0030] The concentration of the acetic acid solution is preferably 0.1-1 mol / L, 0.3-0.7 mol / L, 0.4-0.6 mol / L or 0.5 mol / L.
[0031] The temperature of the acid treatment in step 1) is 0-10°C; preferably 1-8°C, 2-6°C, 3-5°C or 4°C.
[0032] The time of the acid treatment in step 1) is preferably at least 12 hours; more preferably 12 to 36 hours, 18 to 30 hours, 22 to 26 hours or 24 hours.
[0033] The amount of water in step 2) is preferably calculated based on the volume of water being 10 to 30 times, or 10 to 20 times, or 10 times the volume of the mixed paste.
[0034] The centrifugation temperature in step 2) is preferably 4°C.
[0035] The centrifugal force of the centrifugation in step 2) is preferably 15,000-50,000×g, 20,000-35,000×g or 25,000×g.
[0036] The centrifugation time in step 2) is preferably 5 to 45 minutes, 10 to 30 minutes or 15 minutes.
[0037] The inorganic salt described in step 3) is preferably at least one of sodium sulfate, ammonium sulfate, potassium chloride and sodium chloride.
[0038] The dosage of the inorganic salt is preferably calculated based on the final concentration of 0.5-4.0M, 0.5-1.5M, 0.9M.
[0039] The standing time in step 3) is preferably 6 to 24 hours, 6 to 12 hours or 12 to 18 hours.
[0040] The centrifugal force of the centrifugation in step 3) is preferably 4,000-8,000×g, 5,000-6,000×g, 5,500×g.
[0041] The centrifugation time in step 3) is preferably 5 to 45 minutes, 10 to 30 minutes or 15 minutes.
[0042] The acidic solution in step 4) is preferably an acetic acid solution; its concentration is preferably 0.1-1M, 0.3-0.7M or 0.5M.
[0043] The amount of the acidic solution used in step 4) is preferably such that the collagen-containing precipitate is fully dissolved.
[0044] The dialysis in step 4) preferably uses a dialysis tube or dialysis bag with a specification of 10K.
[0045] The dialysis steps described in step 4) are as follows: first dialyze with an acetic acid solution with a concentration of 0.01 to 0.3 mol / L, and then dialyze with water.
[0046] The water described in the present invention is preferably at least one of deionized water, distilled water and ultrapure water.
[0047] The non-mammalian source collagen is composed of smaller collagen fibrils and has better absorbability; it also maintains a triple helix structure with biological activity.
[0048] The main component of the calcium phosphate powder described in step (1) and step (3) is single-phase hydroxyapatite, and its particles are powders that can pass through sieves with pore sizes of 20 μm, 5 μm, and 1.25 μm; preferably, the powders can pass through a sieve with a pore size of 20 μm.
[0049] The calcium phosphate powder is preferably prepared by the following steps:
[0050] (A) calcining the fish scale at 550-1250° C. for 30 min-1 h, and continuously increasing the temperature at 5-20° C. / min to obtain a calcined sample;
[0051] (B) mixing the sample obtained in step (A) with phosphate buffer to obtain a suspension;
[0052] (C) mixing the mixed liquid in step (B) and zirconium oxide balls, grinding, drying, and sieving to obtain calcium phosphate powder.
[0053] The fish scales in step (A) may be from any bony fish; preferably, they are from farmed bony fish.
[0054] The bony fish is preferably at least one of tilapia (Oreochromis mossambicus), snakehead fish (Channaargus, Channa micropeltes, Channa striata), carp (Cyprinus carpio), grass carp (Ctenopharyngodon idella), silver carp (Hypophthalmichthys molitrix), bighead carp (Hypophthalmichthys nobilis) and Channa micropeltes.
[0055] The phosphate buffer described in step (B) is preferably 1×PBS.
[0056] The amount of the phosphate buffer described in step (B) is preferably calculated based on the solid-liquid ratio of fish scale to phosphate buffer of 1g:5-30mL, 1g:10-15mL, or 1g:10mL.
[0057] The zirconia balls described in step (C) are preferably zirconia balls with a size of 1 to 10 mm, and more preferably zirconia balls with a size of 5 mm.
[0058] The amount of the zirconium oxide balls described in step (C) is calculated based on a mass ratio of fish scale to zirconium oxide balls of 1:5 to 1:20; preferably, the amount of the zirconium oxide balls is calculated based on a mass ratio of fish scale to zirconium oxide balls of 1:5 to 1:20.
[0059] The grinding time in step (C) is preferably 12 to 48 hours, 20 to 28 hours or 24 hours.
[0060] The drying in step (C) is preferably air drying.
[0061] The sieve in the sieving in step (C) preferably has a pore size of 20 μm.
[0062] The concentration of the acetic acid solution in step (1) is preferably 0.1-1 mol / L, 0.3-0.7 mol / L, 0.4-0.6 mol / L or 0.5 mol / L.
[0063] The cross-linking agent described in step (1) and step (3) is a pharmaceutically acceptable chemical reagent, including at least one of glutaraldehyde, 1,4-butanediol diglycidyl ether, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and genipin.
[0064] The concentration of collagen in the pre-solution I described in step (1) is preferably 5-20 mg / mL, 5-15 mg / mL, 10 mg / mL.
[0065] The amount of the calcium phosphate powder in step (1) is preferably calculated based on a mass ratio of the calcium phosphate powder to the collagen of 0.5-2:1, 0.5-1.5:1 or 1:1.
[0066] The amount of the cross-linking agent in step (1) is preferably calculated based on 3-15% or 8-10% of the collagen mass.
[0067] The mixing conditions described in step (2) are preferably stirring at 0-10°C and 100-800 rpm for 12-36 h; more preferably stirring at 2-8°C and 100-500 rpm for 20-28 h; and most preferably stirring at 4°C and 300 rpm for 24 h.
[0068] The shape of the mold described in step (2) can be cylindrical, bullet-shaped or cubic; preferably, it is a bullet-shaped mold with a diameter of 7 mm and a height of 12 mm.
[0069] The concentration of the acetic acid solution in step (3) is preferably 0.1-1 mol / L, 0.1-0.5 mol / L or 0.3-0.5 mol / L.
[0070] The amount of the cross-linking agent in step (3) is preferably calculated based on 3-15% or 8-10% of the collagen mass.
[0071] The concentration of collagen in the pre-solution II in step (3) is preferably 1-15 mg / mL, 1-10 mg / mL or 5 mg / mL.
[0072] The amount of the pre-solution II in step (4) is calculated based on the collagen contained therein being 40-60% of the collagen mass in the scaffold embryo; preferably, it is calculated based on the collagen contained therein being 50% of the collagen mass in the scaffold embryo.
[0073] The standing reaction time in step (4) is preferably 12 to 48 hours, 18 to 32 hours or 24 hours.
[0074] A non-mammalian source collagen porous composite scaffold is obtained by the above preparation method; it is a core-shell structure, the material of the core layer is a material obtained by cross-linking non-mammalian source collagen and calcium phosphate, and the material of the shell layer is non-mammalian source collagen; its compression modulus is 47.47 kPa, and the scaffold porosity is greater than 90%.
[0075] The application of the above-mentioned non-mammalian source collagen porous composite scaffold in the preparation of biomedical engineering materials is particularly suitable for the preparation of oral site preservation and treatment materials.
[0076] Compared with the prior art, the present invention has the following advantages and effects:
[0077] The present invention is based on the high solubility characteristics of non-mammalian collagen, which is a low-viscosity aqueous liquid at 10 mg / mL. It can not only obtain a scaffold with a higher porosity, but also facilitate the collagen solution to penetrate into the pores of the scaffold. The core layer of the scaffold obtained by the double cross-linking technology is a material obtained by cross-linking non-mammalian collagen and calcium phosphate, and the surface of the core layer is wrapped with a collagen layer. While ensuring that the porosity and pore size are not affected, the present invention obtains a new collagen-calcium phosphate composite scaffold with a compression performance three times that of the composite scaffold disclosed in the prior patent, which not only meets the mechanical performance requirements of the composite scaffold for site preservation treatment, but also improves the degradation performance and biological activity of the scaffold, prolongs the action time, optimizes the biological performance, and further expands the application range of the non-mammalian collagen-calcium phosphate composite scaffold. BRIEF DESCRIPTION OF THE DRAWINGS
[0078] Figure 1 This is a photo of collagen under atomic force microscopy (AFM); A is bullfrog collagen ABFC, and B is bovine collagen ABVC.
[0079] Figure 2 This is the SDS-PAGE result of collagen; A is the whole picture, B is a partial screenshot; FC is bullfrog collagen, and VC is bovine collagen.
[0080] Figure 3 It is a diagram of the morphological structure and mechanical properties test results of the scaffold; wherein A is a photo of the scaffold, B is a stress-strain curve diagram of the compression performance of the scaffold, C is a SEM image of the single-crosslinked scaffold Col-HA prepared in Comparative Example 2, and D is a SEM image of the double-crosslinked scaffold dCol-HA prepared in Example 4.
[0081] Figure 4 It is a graph showing the degradation performance test results of the scaffold; wherein A is the rapid degradation experimental results of samples dCol-HA, Col-HA and 15% Col-HA in PBS, and B is the degradation experimental results of samples dCol-HA, Col-HA and Col in artificial saliva.
[0082] Figure 5 The following are the radiographs of the experimental site of the dog (a), the photographs 16 weeks after surgery (b), the CBCT images of the surgical site (c), and the corresponding buccal height data statistics (d).
[0083] Figure 6 The micro-CT image of the experimental site in dogs 16 weeks after surgery (a) and the corresponding statistical data of bone tissue morphological characteristics (b).
[0084] Figure 7The GOLDNER trichrome staining image of the dog's experimental site 16 weeks after surgery (a) and the corresponding statistical graph (b). DETAILED DESCRIPTION
[0085] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.
[0086] Example 1 Extraction of Type I Collagen from Non-Mammalian Sources
[0087] (1) Use pre-cooled deionized water to thoroughly clean the bullfrog (Rana catesbeiana) skin and remove residual impurities. Soak the clean bullfrog skin in a 0.5M (M is the abbreviation for mol / L) NaOH solution. The volume of NaOH solution used is calculated based on the ratio of 1g bullfrog skin: 10mL NaOH solution. Soak at 4°C for 48 hours, and change the solution every 24 hours. Wash the bullfrog skin treated with alkali with pre-cooled deionized water and treat it with HCl solution or deionized water until neutral. Soak the treated bullfrog skin in a 0.5M acetic acid solution for 24 hours at a ratio of 1g bullfrog skin to 10mL acetic acid solution, and then use a mechanical stirrer to fully crush it to obtain a thick collagen paste.
[0088] (2) The collagen paste was diluted with distilled water equivalent to 10 times the volume of the collagen paste, and centrifuged at 4°C and 25,000×g for 15 min. The supernatant was collected to obtain a collagen solution. A NaCl solution with a final concentration of 0.9 M was added to the clarified collagen solution, and the solution was allowed to stand for 24 h to obtain precipitated collagen. The collagen was separated by centrifugation at 5,500×g for 15 min.
[0089] (3) The collagen was redissolved in a 0.5 M acetic acid solution and dialyzed in a 0.1 M acetic acid solution using a 10K MWCO dialysis tube for 48 hours, with the solution being replaced every 24 hours. The solution was then dialyzed in distilled water for 48 hours, with the solution being replaced every 24 hours. The dialyzed solution was freeze-dried to obtain a high-purity non-mammalian type I collagen powder.
[0090] Example 2 Preparation of calcium phosphate powder
[0091] Calcium phosphate powder was extracted from the collected scales of Channa micropeltes. The specific steps are as follows: first, the collected scales were thoroughly cleaned with deionized water, and then placed in a muffle furnace and calcined at 850°C and a constant heating rate of 10°C / min for 1 hour to obtain scales with inorganic matter removed. The heat-treated scales were mixed with 1×PBS solution at a ratio of 1g scales to 10mL 1×PBS solution, and 5mm zirconium oxide balls were added at a ratio of 1g scales to 10g zirconium oxide balls, and the mixture was fully ball-milled for 24 hours and then air-dried. The air-dried powder was sieved with a metal sieve with an aperture of 20μm to obtain calcium phosphate powder.
[0092] Example 3 Characterization of Type I Collagen from Non-Mammalian Origins
[0093] (1) The collagen powder prepared in Example 1 was dissolved in a 0.1 M acetic acid solution and then stirred thoroughly overnight at 4° C. Finally, the mixture was centrifuged at 4000 rpm at 4° C. for 90 minutes, and the supernatant was collected.
[0094] (2) Drop the bullfrog collagen supernatant obtained in step (1) on a mica sheet, spread it flat and air-dry it. Use an atomic force microscope (AFM) in tapping mode to detect the morphology and structure of collagen. The test results show that bullfrog collagen directly presents a collagen fibril structure with a diameter of about 100 to 300 nm, such as Figure 1 shown.
[0095] (3) Mix the bullfrog collagen supernatant obtained in step (1) with the same volume of 1×SDS (sodium dodecyl sulfate) loading solution, and then heat at 95°C for 5 minutes. Take 10 μL of the above solution and a suitable protein marker and drop it onto a polyacrylamide gel (electrophoresis gel), run it at 0.2A for 2 hours, and then stain it in Coomassie Brilliant Blue staining solution for 1 hour to obtain a visualized protein band of bullfrog collagen. Figure 2 As shown, the obtained bullfrog collagen maintains a triple helical structure with biological activity.
[0096] Example 4 Preparation and characterization of porous composite scaffolds derived from non-mammalian collagen
[0097] (1) The collagen powder prepared in Example 1 was dissolved in a 0.5M acetic acid solution, and then the calcium phosphate powder prepared in Example 2 was added in a mass ratio of 1:1 between collagen and calcium phosphate, and then a BDDE cross-linking agent equivalent to 10% of the mass of the collagen powder was added to obtain a pre-solution I with a collagen concentration of 10 mg / mL. The pre-solution I was stirred at 300 rpm at 4°C for 24 hours, and then transferred to a bullet-shaped mold with a depth of 12 mm and a maximum diameter of 7 mm. Freeze drying was performed to obtain a non-mammalian source collagen porous composite scaffold embryo, also known as Col-HA.
[0098] (2) The collagen prepared in Example 1 was prepared with a 0.5M acetic acid solution to obtain a collagen solution with a concentration of 5 mg / mL, and then a BDDE cross-linking agent equivalent to 10% of the mass of the collagen powder was added to obtain a pre-solution II. The pre-solution II with the same volume as the pre-solution I was injected into the mold, and the non-mammalian collagen porous composite scaffold embryo was slowly immersed in the mold, allowed to stand at 4°C for 24 hours, and then freeze-dried to obtain a non-mammalian collagen porous composite scaffold dCol-HA for preserving the alveolar ridge site.
[0099] (3) For better comparison, the following samples were prepared:
[0100] 1) Preparation of pure collagen scaffold Col: The collagen powder prepared in Example 1 was dissolved in a 0.5M acetic acid solution, and then a cross-linking agent 1,4-butanediol diglycidyl ether (BDDE) equivalent to 10% of the mass of the collagen powder was added to obtain a pre-solution with a collagen concentration of 10 mg / mL. The pre-solution was stirred at 300 rpm at 4°C for 24 hours, and then transferred to a bullet-shaped mold with a depth of 12 mm and a maximum diameter of 7 mm. Freeze-dried to obtain a non-mammalian source collagen porous scaffold Col.
[0101] 2) Prepare a scaffold 15% Col-HA treated with the same crosslinker content as dCol-HA: Dissolve the collagen powder prepared in Example 1 in 0.5M acetic acid solution, then add the calcium phosphate powder prepared in Example 2 at a mass ratio of 1:1 between collagen and calcium phosphate, and then add a crosslinker 1,4-butanediol diglycidyl ether (BDDE) equivalent to 15% of the mass of the collagen powder to obtain a pre-solution with a collagen concentration of 10 mg / mL. The pre-solution was stirred at 300 rpm for 24 hours at 4°C and then transferred to a bullet-shaped mold with a depth of 12 mm and a maximum diameter of 7 mm. Freeze-dry to obtain a non-mammalian source collagen porous composite scaffold 15% Col-HA.
[0102] The obtained samples Col-HA and dCol-HA were cut transversely, fixed on the sample stage, and sprayed with gold at 20mV for 15s. The sample surface was then observed using a field emission scanning electron microscope (FESEM) at an accelerating voltage of 3kV. Figure 3 As shown in the figure, Col-HA and dCol-HA samples are yellow-white sponge-like cylinders with a pore structure of 20 to 100 μm. Hydroxyapatite particles are attached to the surface of collagen. The pore structure of dCol-HA is consistent with that of the single-cross-linked sample Col-HA.
[0103] The obtained sample was loaded on a universal testing machine and compressed to 90% of its original height at a rate of 2 mm / min using a 10 kN load cell to obtain a stress-strain curve (e.g. Figure 3 As shown in the figure, the initial gradient of the stress-strain curve was then measured, and the compression modulus (stress-to-strain value) of dCol-HA was 47.47 kPa, and the compression modulus of Col-HA was 16.57 kPa. It can be seen that the double-crosslinked sample dCol-HA is 3 times that of the single-crosslinked sample Col-HA.
[0104] The porosity of the obtained sample was measured by the liquid displacement method. The sample was immersed in a glass bottle containing a known volume of anhydrous ethanol (V1) for 5 minutes, and the total volume V2 was recorded. Subsequently, the sample that had fully absorbed ethanol was removed from the glass bottle, and the volume of ethanol involved was recorded as V3. The porosity of dCol-HA and Col-HA scaffolds was calculated according to the following formula and was greater than 90%.
[0105]
[0106] The in vitro biodegradation behavior of the samples was determined by the protein content in the sample solution at different time points after PBS immersion, and the degradation rates of the samples dCol-HA, Col-HA and 15% Col-HA were detected. In short, samples with known protein content (W0) were placed in 6-well cell culture plates and incubated in PBS at 37°C for 7 days. The PBS solution of part of the scaffold was collected every 2 days and supplemented with the same volume of PBS solution. The collected PBS solution was detected using a BCA kit to obtain the protein content (Wb) in the solution.
[0107] The degradation rate is calculated by the following formula, and the degradation curve is as follows: Figure 5 As shown in A.
[0108]
[0109] Artificial saliva was used to simulate the degradation behavior in the oral cavity. The detection principle was consistent with the PBS rapid degradation experiment, and the degradation rates of samples dCol-HA, Col-HA and Col were detected. Samples with known protein content (W0) were placed in a 6-well cell culture plate and incubated in artificial saliva at 37°C for 14 days. Part of the solution in which the scaffold was soaked was collected on the 3rd, 5th, 7th, 10th, 12th and 14th days, and the same volume of artificial saliva solution was supplemented. The collected artificial saliva solution was detected using the BCA kit to obtain the protein content in the solution (Wb). The degradation rate was calculated by the following formula, and the degradation curve is shown in the figure. Figure 5 As shown in B.
[0110]
[0111] The results show that in the PBS rapid degradation experiment, the degradation rate of the two-step cross-linked sample dCol-HA is lower than that of the single-cross-linked sample Col-HA; the one-step cross-linked sample with the same cross-linker content did not show better degradation performance, indicating that simply increasing the cross-linker concentration cannot directly improve the scaffold performance. In artificial saliva, the degradation curve of the two-step cross-linked sample in the first two weeks is consistent with the curve of the collagen sample, indicating that during this period, the two-step cross-linked sample dCol-HA will show similar degradation characteristics as the collagen sample in the oral cavity, and the consistency of structure and mechanical properties is improved; the one-step cross-linked sample Col-HA degrades rapidly at a rate far exceeding the two-step cross-linked sample dCol-HA and collagen sample, and cannot fully match the tissue regeneration rate, and cannot maximize the use of the scaffold's characteristics to promote the regeneration and repair of alveolar defects; the pure collagen scaffold Col has the slowest degradation rate in artificial saliva because there are no cavities and cracks caused by hydroxyapatite particles occupying the space.
[0112] Example 5 Alveolar ridge site preservation treatment experiment based on canine model
[0113] (1) The alveolar ridge preservation treatment experiment of the canine model was conducted in full compliance with animal ethics review and animal welfare. Six male beagle dogs aged approximately 18 months were purchased (Guangzhou General Research Institute of Pharmaceutical Research Co., Ltd., license number: SCXK (Yue) 2023-0007) and transported to the experimental site for quarantine and adaptation 7 days before surgery. During this period, the beagle dogs' mouths were fully cleaned. The experimental dogs were anesthetized by subcutaneous injection of atropine sulfate (0.05 mg / kg) and intravenous injection of thiopental sodium (25 mg / mL / kg), and the experimental dogs were intubated to inhale a mixed gas (oxygen, nitrogen) and sevoflurane (0.5% to 1.5%) to maintain the anesthesia effect. The gas flow rate was 10-15 mL / kg and the inhalation frequency was 18-22 times / min.
[0114] (2) The right M1 molars of 6 experimental dogs were extracted without flap (see the experimental site for details). Figure 5 In (a)), the M1 molar was cut in half using a dental fissure drill, the proximal root was extracted, the distal root was retained, and root canal treatment was performed on the distal root, which was cleaned and perfused with gutta-percha. The proximal root defect was rinsed with normal saline, and then the porous composite scaffold prepared in Example 4 was gently inserted and sutured with absorbable sutures. The same surgical operation was performed on the left M1 molars of the three experimental dogs. The proximal root defect was rinsed with normal saline and sutured in the same way. The dogs recovered well 4 weeks after the operation, with no redness, swelling or inflammation at the surgical site. Figure 5 As shown in (b) in .
[0115] (3) The same surgical operation was performed on the left M1 molars of the remaining three experimental dogs in Example 4. After the non-flap tooth extraction surgery was completed, the M1 molar was cut in half using a dental fissure drill, the proximal root was extracted, the distal root was retained, and the distal root was treated with root canal therapy, cleaned and perfused with gutta-percha. The proximal root defect was rinsed with saline, and then a benchmark product with 90% bovine bone powder and 10% collagen as components was gently inserted, and sutured with the same absorbable suture. The surgical site of the experimental dog healed well, and there was no inflammation or swelling caused by the sample, indicating that the sample had good biocompatibility and no obvious toxic effect on organisms.
[0116] Example 6 In vivo cone beam CT scanning
[0117] In vivo cone beam CT scans were performed on the surgical site before and immediately after surgery, and at 2 weeks, 4 weeks, 8 weeks, 12 weeks, and 16 weeks. After the experimental dogs were given general anesthesia, low-dose cone beam CT imaging was performed on the surgical site, and the obtained CT images were measured, specifically: ① lingual alveolar ridge height, ② buccal alveolar ridge height, ③ alveolar ridge width corresponding to 1, 3, and 5 mm below the residual highest alveolar ridge. By comparing CT images at different time periods, the changes in alveolar bone height and width at the surgical site were obtained, see Figure 5 As shown in (c) in .
[0118] Experiments have shown that non-mammalian type I collagen porous composite scaffolds can significantly inhibit the atrophy of the buccal alveolar ridge ( Figure 5 In (d), the height and width of the alveolar ridge shrink less than the blank group without implant, which is consistent with the efficacy of the control group implanted with the benchmark product, maintaining the size of the alveolar ridge. The ability of the non-mammalian type I collagen porous composite scaffold to preserve the alveolar ridge site is confirmed.
[0119] Example 7 Micro-CT
[0120] 16 weeks after surgery, the experimental dogs were sacrificed and their mandibles were removed and fixed in 10% formalin fixative for 24-48 hours. The entire defect in the model was selected as the analysis area for micro-CT photography and three-dimensional reconstruction using professional image analysis software. The reconstructed three-dimensional images were quantitatively analyzed to obtain the bone volume fraction (BV / TV), bone density (BMD) and morphological characteristics of trabeculae (Tb.N, Tb.Sp) of the experimental site, and corresponding statistics were performed. The experimental results are shown in the figure. Figure 6 The results showed that the defect of the right M1 molar implanted with non-mammalian type I collagen porous composite scaffold had higher bone density in the new bone area compared with the blank group, and the trabecular morphology was close to the ideal plate shape, with high trabecular density and quantity, which was close to the efficacy of the benchmark product. In addition, the new bone area of the benchmark product group contained more exogenous minerals left in the sample, while the non-mammalian type I collagen porous composite scaffold can promote the generation of more endogenous new bone.
[0121] Example 8 Tissue Slice Staining Analysis
[0122] After fixation in 10% formalin, the mandibular samples were transferred to 8% formic acid for decalcification for 14 days. The samples were dehydrated and embedded in paraffin. The cross-sections were sampled at the center of the defect to obtain defect sections with a thickness of 3.5 μm. The sections were stained with GOLDNER trichrome and quantitatively and qualitatively analyzed for new bone formation, the number of new blood vessels, and sample residues according to ISO 10993-6:2016. The experimental results are shown in Figure 7 As shown: Compared with the blank group, the non-mammalian type I collagen porous composite scaffold group has a higher proportion of new bone in the defect area, which is consistent with the efficacy of the benchmark product. In addition, the number of new blood vessels in the defect area implanted with the non-mammalian type I collagen porous composite scaffold increased significantly compared with the blank group and the benchmark product group, which is about twice that of the other groups. This shows that the core-shell structure formed by non-mammalian type I collagen effectively improves the biological activity of the scaffold, and can promote blood vessels to penetrate into the interior of the scaffold during the healing stage, accelerating the regeneration and healing of bone tissue in the defect area. In addition, it can be seen that more than 2% of exogenous minerals remain in the defect area of the benchmark product group 16 weeks after surgery. The actual new bone generation capacity is similar to that of the non-mammalian type I collagen porous composite scaffold, and the results are consistent with micro-CT.
[0123] Comparative Example 1 Characterization of bovine type I collagen
[0124] (1) The purchased bovine Achilles tendon collagen was dissolved in 0.1 M acetic acid solution and then stirred well overnight at 4° C. Finally, the mixture was centrifuged at 4000 rpm at 4° C. for 90 minutes, and the supernatant was collected.
[0125] (2) Drop the bovine Achilles tendon collagen supernatant obtained in step (1) on a mica sheet, spread it flat and air-dry it. Use an atomic force microscope (AFM) in tapping mode to detect the collagen morphology. The test results show that the bovine Achilles tendon collagen fiber structure is clear, with a diameter of 1.5 μm, such as Figure 1 shown.
[0126] (3) Mix the bovine collagen supernatant obtained in step (1) with the same volume of 1×SDS (sodium dodecyl sulfate) loading solution, and then heat at 95°C for 5 minutes. Take 10 μL of the above solution and a suitable protein marker and drop it onto a polyacrylamide gel (electrophoresis gel), run it at a current of 0.2A for 2 hours, and then stain it in Coomassie Brilliant Blue staining solution for 1 hour to obtain a visualized protein band of bovine collagen. Figure 2 As shown, the obtained bovine collagen maintains a triple helical structure with biological activity.
[0127] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a porous composite scaffold of non-mammalian collagen, characterized in that The steps include: (1) dissolving non-mammalian collagen in an acetic acid solution, then adding calcium phosphate powder and mixing, and then adding a cross-linking agent to obtain a pre-solution I; (2) After the pre-solution I is fully mixed at 0-10° C., it is added into the mold and freeze-dried to obtain a scaffold embryo; (3) dissolving non-mammalian collagen in an acetic acid solution, and then adding a cross-linking agent to obtain a pre-solution II; (4) Injecting the pre-solution II into the scaffold embryo obtained in step (2), allowing to react at 0-10° C., and freeze-drying to obtain a non-mammalian collagen porous composite scaffold.
2. The method for preparing the non-mammalian collagen porous composite scaffold according to claim 1, characterized in that: The non-mammalian collagen described in step (1) and step (3) is prepared by the following steps: 1) Cleaning the fresh raw material from non-mammals, sequentially subjecting it to alkali treatment, washing, acid treatment, and mechanical crushing to obtain a mixed paste; 2) diluting the mixed paste obtained in step 1) with water, and then centrifuging at 2-8° C. to obtain an upper layer solution containing collagen and a pellet containing pigment, and collecting the upper layer solution containing collagen; 3) adding an inorganic salt to the upper layer solution obtained in step 2), mixing well and then standing to obtain a precipitate containing collagen, and collecting the precipitate by centrifugation; 4) mixing the collagen-containing precipitate obtained in step 3) with the acidic solution to obtain a mixed solution containing free collagen; The mixed solution containing free collagen is dialyzed to obtain a non-mammalian collagen solution, which is freeze-dried to obtain non-mammalian collagen.
3. The method for preparing the non-mammalian collagen porous composite scaffold according to claim 2, characterized in that: The non-mammal mentioned in step 1) is a frog culture species; The raw material in step 1) is skin; The amount of water used in step 2) is calculated based on the volume of water being 10 to 30 times the volume of the mixed paste; The inorganic salt in step 3) is at least one of sodium sulfate, ammonium sulfate, potassium chloride and sodium chloride; The dosage of the inorganic salt is calculated based on its final concentration of 0.5 to 4.0 M; The acidic solution described in step 4) is an acetic acid solution; The dialysis described in step 4) is performed using a dialysis tube or dialysis bag with a specification of 10K.
4. The method for preparing the non-mammalian collagen porous composite scaffold according to claim 2, characterized in that: The specific steps of the alkaline treatment in step 1) are as follows: soaking the cleaned fresh non-mammalian raw material in an alkaline solution; The temperature of the alkali treatment in step 1) is 0 to 10°C; The alkali treatment time in step 1) is at least 24 hours; The specific steps of the acid treatment in step 1) are as follows: soaking the washed raw material in an acidic solution; The temperature of the acid treatment in step 1) is 0 to 10°C; The acid treatment time in step 1) is at least 12 hours; The centrifugal force of the centrifugation in step 2) is 15,000 to 50,000×g; The centrifugation time in step 2) is 5 to 45 minutes; The standing time in step 3) is 6 to 24 hours; The centrifugal force of the centrifugation in step 3) is 4,000 to 8,000×g; The centrifugation time in step 3) is 5 to 45 minutes; The dialysis steps described in step 4) are as follows: first dialyze with an acetic acid solution with a concentration of 0.01 to 0.3 mol / L, and then dialyze with water.
5. The method for preparing the non-mammalian collagen porous composite scaffold according to claim 1, characterized in that: The main component of the calcium phosphate powder described in step (1) and step (3) is single-phase hydroxyapatite.
6. The method for preparing the non-mammalian collagen porous composite scaffold according to claim 5, characterized in that: The calcium phosphate powder is prepared by the following steps: (A) calcining the fish scale at 550-1250° C. for 30 min-1 h, and continuously increasing the temperature at 5-20° C. / min to obtain a calcined sample; (B) mixing the sample obtained in step (A) with phosphate buffer to obtain a suspension; (C) mixing the mixed liquid in step (B) and zirconium oxide balls, grinding, drying, and sieving to obtain calcium phosphate powder.
7. The method for preparing the non-mammalian collagen porous composite scaffold according to claim 6, characterized in that: The fish scales in step (A) are from any bony fish; The phosphate buffer described in step (B) is 1×PBS; The amount of the phosphate buffer described in step (B) is calculated based on the solid-liquid ratio of fish scale to phosphate buffer of 1 g: 5 to 30 mL; The zirconia balls described in step (C) are zirconia balls with a size of 1 to 10 mm; The amount of the zirconium oxide balls described in step (C) is calculated based on a mass ratio of fish scale to zirconium oxide balls of 1:5 to 1:20; The grinding time in step (C) is 12 to 48 hours; The drying in step (C) is air drying; The sieve in the sieving step (C) has a pore size of 20 μm.
8. The method for preparing the non-mammalian collagen porous composite scaffold according to claim 1, characterized in that: The concentration of the acetic acid solution in step (1) is 0.1 to 1 mol / L; The cross-linking agent in step (1) and step (3) is at least one of glutaraldehyde, 1,4-butanediol diglycidyl ether, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and genipin; The concentration of collagen in the pre-solution I described in step (1) is 5 to 20 mg / mL; The amount of calcium phosphate powder described in step (1) is calculated based on a mass ratio of calcium phosphate powder to collagen of 0.5 to 2:1; The amount of the cross-linking agent in step (1) is calculated based on 3 to 15% of the mass of the collagen; The mixing conditions in step (2) are stirring at 0-10° C. and 100-800 rpm for 12-36 hours; The shape of the mold in step (2) is cylindrical, bullet-shaped or cubic; The concentration of the acetic acid solution in step (3) is 0.1 to 1 mol / L; The amount of the cross-linking agent in step (3) is calculated based on 3 to 15% of the mass of the collagen; The concentration of collagen in the pre-solution II described in step (3) is 1 to 15 mg / mL; The amount of the pre-solution II in step (4) is calculated based on the collagen contained therein being 40-60% of the collagen mass in the scaffold embryo; The standing reaction time in step (4) is 12 to 48 hours.
9. A non-mammalian collagen porous composite scaffold, characterized in that: It is obtained by the preparation method according to any one of claims 1 to 8; it is a core-shell structure, the core layer material is a material obtained by cross-linking non-mammalian collagen and calcium phosphate, and the shell layer material is non-mammalian collagen.
10. Use of the non-mammalian collagen porous composite scaffold according to claim 9 in the preparation of biomedical engineering materials.
Citation Information
Patent Citations
Composite scaffold material
CN115397920A
Composite scaffold material
US20230158212A1